Lithium Extraction Techniques and the Application Potential of Different Sorbents for Lithium Recovery from Brines. (19th May 2023) - Reich, Rebekka; Slunitschek, Klemens; Danisi, Rosa Micaela; Eiche, Elisabeth; Kolb, Jochen
ABSTRACT: Geothermal power plants produce large amounts of high-temperature fluids from variable depths. These fluids can be enriched in lithium to up to 240 mg/L, rendering them an exploitable resource, not yet processed at industrial scale. The pressure on Li demand is expected to increase in the future, making the technical degradability of new Li resources indispensable. We examine Li-extraction methods from aqueous solutions systematically, dealing with evaporation, direct precipitation, membrane-related processes, solvent extraction, sorption, and ion exchange. Sorption and ion-exchange techniques are regarded to be the most promising methods with a high potential for the feasible lithium extraction. Therefore, Li sorption on different inorganic sorbents, in particular for the implementation into operating geothermal power plants, is evaluated. Inorganic sorbents, such as lithium–manganese oxide, titanium oxide, aluminum hydroxide, iron phosphate, clay minerals, and zeolite group minerals besides other sorbents, e.g. zirconium phosphate, tin antimonate, antimony oxide, tantalum oxide, and niobium oxide, are regarded. Promising inorganic sorbents for an environmentally friendly, efficient, and selective Li extraction are lithium–manganese oxide, iron phosphate, or zeolite. To evaluate the effectiveness of these sorbents to large-scale industrial Li2 CO3 (or LiOH) production, we highlight their potential advantages and disadvantages in the application under geothermal operating conditions.